The tourist plot: Antarctica and the modernity of nature - Picard, David (2018)
The work explores contemporary Antarctic tourism practices through the lens of the dramaturgic concept of ‘plot’. Plot refers to a socially construed narrative structure that allows social actors to frame their participation in social life through socially held scenarios, stories and cosmologies. Drawing on fieldwork carried out in the Argentinian harbor town of Ushuaia, the authors demonstrate that Antarctic tourists, despite the variety of their experiences, existences and travel motifs, follow, to a very large degree, the same ‘plot’. This leads them through a dialectical journey, departing from a ‘modern’ life-world of home towards and beyond the presumed boundaries of ‘civilization’, to become immersed in a magical, weird, and wonderful ur-nature found in the White continent, and then back home. The authors argue that this plot, through its specific dramaturgic configuration and settings, pulls to the surface a wider ontological and cosmological order underlying modern tourism and social life at large.